ANALISIS ESTIMASI COST-VOLUME-PROFIT (CVP) DALAM HUBUNGANNYA DENGAN PERENCANAAN LABA PADA HOTEL TLOGO MAS SARANGAN - Satrijo Budi Wibowo (Assets: Jurnal Akuntansi dan Pendidikan, 2012)
This research aims to analyze the estimated Cost-Volume-Profit (CVP) in association with the Profit Planning at Tlogo Mas Hotel Sarangan. Analytical techniques used in this study were: (1) Classify all costs incurred in the variable costs (variable costs) and fixed costs (fixed cost). (2) Method of least squares analysis. (3) Analysis of the breakeven point (Break Event Point / BEP). The results showed that Tlogo Mas Hotel Sarangan determine the profits of 10% of total sales. It is seen from the fluctuations experienced profit growth each year from 2009 to 2011.